Unveiling immunogenic characteristics and neoantigens in endometrial cancer with POLE hotspot mutations for improved immunotherapy - Jian Huang; Shuangna Song; Yihua Yin; Yinyan He; Huimin Wang; Ye Gu; Laman He; Xintao Wang; Xiaocao Miao; Zhigang Zhang; Xueli Zhang; Yiran Li; et al. (Frontiers in Immunology)
BackgroundImmunotherapy, especially with the use of immune checkpoint inhibitors, has demonstrated efficacy for a variety of malignant tumors. However, the potential of immunotherapy for endometrial cancer (EC) with POLE mutations remains underexplored.MethodsWe utilized multiple databases and clinical specimens to investigate the immunogenicity profiles of EC patients carrying POLE mutations. One particular hotspot mutation POLEP286R was identified and further studied. Consequently, by constructing human leukocyte antigen (HLA) tetramers and incubating them with patients’ peripheral blood mononuclear cells (PBMCs), T cells capable of recognizing the POLEP286R mutation were sorted for further transcriptomic, proteomic and T-cell receptor (TCR) sequencing analyses and for an organoid EC model.ResultsTumor- and immune-related pathways were shown to be activated in the POLEP286R mutant group. Importantly, by using an organoid model of EC, we further confirmed the antitumor potential of T cells that were specific to the POLEP286R mutation.ConclusionsOur study uncovers the pronounced immunogenicity of POLE-mutant EC and characterizes neoantigens that are unique to the POLEP286R mutation, thus providing a promising new immunotherapeutic strategy for EC.